2007
DOI: 10.1620/tjem.211.15
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Day-Service in Maintaining General Nutritional Status in Elderly Japanese: A Longitudinal Study

Abstract: Day-service, commuting service for elderly people requiring care at home, is one healthcare option in Japan. To date, however, there exist no studies that have examined the effects of day-service use on health outcomes in Japan. The objective of the present longitudinal study was to determine whether there is an association between day-service use and various physical and mental health outcomes in elderly people requiring care. The subjects were 61 elderly persons who required between 25 and 49 min of assistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…When serum albumin decreased by 1 g/L, the odds of being classified as malnourished increased 1.1-fold (25); thus, serum albumin is a marker of nutrition status (26). The present study showed that dietary MCT improved plasma albumin concentration compared with LCT (Table 3), similar to the results of a previous study (5,6).…”
Section: Discussionsupporting
confidence: 86%
“…When serum albumin decreased by 1 g/L, the odds of being classified as malnourished increased 1.1-fold (25); thus, serum albumin is a marker of nutrition status (26). The present study showed that dietary MCT improved plasma albumin concentration compared with LCT (Table 3), similar to the results of a previous study (5,6).…”
Section: Discussionsupporting
confidence: 86%
“…When serum albumin decreased by 1 g/l, the odds of being classified as malnourished increased 1.1 times [ 5 ]. So, serum albumin is a marker of nutritional status [ 12 ]. In this study, serum albumin concentration was higher in the MCT group than in the LCT group, suggesting that nutritional status of the MCT group was improved.…”
Section: Discussionmentioning
confidence: 99%
“…For those who need assistance with daily living activities, a successful approach has been to transport the elderly to community‐based centres, where lunch, snacks, bathing, professional consultations, rehabilitation and recreational activities are provided during daytime hours. A two‐year longitudinal study in Japan has shown that adult daycare service is useful in maintaining nutritional status 69 . The booming population of elderly persons is also bringing about new business opportunities for food services targeting older consumers 70 .…”
Section: Increased Risk Of Malnutrition and In The Elderlymentioning
confidence: 99%